Participation and collaborative Governance - Bouckaert, Geert (Revista del CLAD Reforma y Democracia, 2025)
Democracy implies participation and gains legitimacy by adding collaborative governance. This enhances trust in all three stages of participation: informing, consulting, and engaging. However, cultures of participation and collaboration matter in the interactions of citizens, politics, and administrations. A special focus is needed for situations of crises. A general focus is needed at the micro, the meso, and the macro level to ensure resilience.
Keywords: Participation; collaboration; governance; democracy; informing; consulting; engaging